Dexamethasone Pulse Therapy in Pemphigus Vulgaris Associated Myocardial Infarction in Resource-Limited Settings - Vikash Paudel (Nepal Journal of Dermatology, Venereology & Leprology)
Pemphigus vulgaris is an autoimmune blistering disorder where biologics are the cornerstone of therapy. In resource-limited settings, a dermatologist should rely on systemic steroids. Dexamethasone pulse therapy is a cheap and established treatment of pemphigus where a supra-pharmacological dose of dexamethasone is used. High dose of dexamethasone is supposed to have atherogenic potential which could promote a hypercoagulable state. Here, we report a case of a 30-year-old woman in the resource-limited setting of Nepal, who was under monthly dexamethasone pulse therapy for pemphigus vulgaris, who had an acute episode of ST-segment elevated myocardial infarction. In such setting, although steroids are the cornerstone of therapy in various disorders, physicians should be equally cautious in using a high dose of steroids which might lead to fatal complications. This could probably be the first case report of steroid-induced acute myocardial infarction during treatment of pemphigus worldwide.